Utility of bronchoalveolar lavage in diagnosing respiratory tract infections in patients with hematological malignancies: are invasive diagnostics still needed? - Tobias Svensson; Kristina Lamberg Lundström; Martin Höglund; Honar Cherif (Upsala Journal of Medical Sciences, 2017)
Background: Patients treated for hematological malignancies have an increased risk of serious infections. Diagnosis and prompt initiation of therapy are essential. Bronchoalveolar lavage (BAL) is a well-established investigation for identifying the cause of pulmonary infiltrates in immunocompromised patients. The aim of the study was to determine the diagnostic yield of BAL in patients treated for hematological malignancies and how often it contributed to a modification of the anti-infectious therapy. Methods: We reviewed records from 151 consecutive BAL procedures in 133 adult patients with hematological malignancies, treated at a tertiary hematology unit from 2004 to 2013. Extensive microbiological work-ups on BAL samples had been performed according to a standardized protocol. Results: A microbiological finding causing the infectious episode could be identified in 59 (39%) cases. In 44 (29%) of the cases, results from BAL had an impact on clinical management either by contributing to a specific diagnosis (25%) or by leading to cessation of ongoing microbiological therapy. The most common diagnoses were invasive pulmonary aspergillosis (IPA) and Pneumocystis jirovecii pneumonia (PJP). Diagnoses of IPA and PJP were based on results from BAL in 65% and 93% of cases, respectively. Several microbiological tests on BAL samples rendered no positive results. Complications were few and mainly mild. Conclusion: BAL is still important for either verifying or excluding some of the most important respiratory tract pathogens in patients with hematological malignancies, particularly IPA and PJP. Standardized procedures for BAL sampling should be continually revised to exclude unnecessary microbiological tests.